Sharia Investment: The Best Choice Or Burden In The Future - Rosidah, Rosidah; Negarawati, Esa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Sharia investment is increasingly gaining attention throughout the world as an investment alternative that is in accordance with Islamic principles. This article aims to analyze whether sharia investment is the best choice or a burden in the future. By examining financial aspects, regulations and their impact on the global economy, this research evaluates the potential and challenges of sharia investment in the ever-growing global market. The main focus of this article is to understand how the Islamic investment market can develop amidst increasingly dominant conventional financial market trends, as well as identifying challenges that investors and policy makers may face. The analysis results show that although sharia investment offers significant advantages in terms of compliance with moral and ethical values, there are several obstacles that must be overcome, such as product and liquidity limitations. Thus, sharia investment could be the best choice in the future if it can overcome these challenges and adapt to increasingly complex market needs.